AljabarMath: The way to foster critical thinking ability - Syaras, Arfina Sukma; Mirza, Ade; Siregar, Nurfadilah; Suratman, Dede (Universitas Ahmad Dahlan, 2024)
Critical thinking ability are important for facing challenges in the 21st century. There are ways to foster critical thinking ability, one of which is through mathematics using learning media. This paper provides an overview of how to foster critical thinking ability, especially among students who used to learn media AljabarMath. This study aims to describe the level of students’ critical thinking ability in mathematics especially algebra subject grades VII SMP Negeri 10 Pontianak by using the AljabarMath. The method used is quantitative descriptive research. Data analysis was done to determine the percentage of critical thinking ability achieved based on indicators measured following the use of AljabarMath. The findings show that: 1) 68% of students were able to comprehend and articulate the purpose of a problem by identifying what was known and asked; 2) 64% of students were able to make a mathematical model in order to identify the relationship between statements, questions, and concepts given in the questions indicated.; 3) students who demonstrated the ability to assess the veracity of statements using the appropriate technique by 64%; and 4) students who demonstrated the ability to make accurate conclusions by taking into account pertinent information and the implications of a problem based on the available data by 62%. The utilization of AljabarMath can enhance students' critical thinking ability in algebra classes, according to the study's findings.